Optimization of thermo-hydraulic performance in partially copper-foam-filled rectangular channels: Experimental insights on foam layer configurations - Kadhim Al-Chlaihawi; Moayed Hasan; Ali Ekaid (International Journal of Thermofluids)
This study presents experimental observations of the heat transfer coefficient and pressure drop undergoing turbulent air flow through a copper metallic foam sample with a porosity of 0.9 and a pore density of 10 PPI, arranged in five distinct configurations within a rectangular channel. The experiments were performed within a hydraulic diameter-based Reynolds number range of 4000 to 16,000, which corresponds to an air frontal velocity range of 2.5 to 5 m/s. The average Nusselt number (Nu), friction factor (f), permeability, inertia coefficient, and thermal-hydraulic enhancement factor were found by analyzing the collected data of heat transfer and pressure drop. The results indicated that the inclusion of metal foam resulted in a 4.8 to 10.5 fold increase in Nu and approximately 12.6 to 60.4 fold increase in friction factor compared to the empty channel. The backward-facing chamfered foam block exhibited the highest thermo-hydraulic enhancement factor, reaching approximately 2.94 at a Reynolds number of 16,000.